Antibacterial, antitubercular, antimalarial and cytotoxic substances from the endophytic Streptomyces sp. TBRC7642. (April 2020) - Bunbamrung, Nantiya; Intaraudom, Chakapong; Dramae, Aibrohim; Thawai, Chitti; Tadtong, Sarin; Auncharoen, Patchanee; Pittayakhajonwut, Pattama
Abstract: Eight previously undescribed naturally-occurring compounds, including abyssomycins Y - Z, methyl aeruginoate, desferri-ferrithocin-4-hydroxyphenethylester, streptomethiocins A - B, furaquinocin I, and streptolactone, along with eleven known compounds were isolated from the endophytic Streptomyces sp. TBRC7642. The chemical structures were determined based on spectroscopic means including 1D, 2D NMR spectroscopy and mass spectrometry. The absolute configurations were assigned by relying on CD spectra and their optical rotations. In addition, the isolated compounds were evaluated for biological activity, such as antimalarial, antitubercular, antibacterial (both Gram-positive and Gram-negative bacteria), as well as for cytotoxicity against MCF-7, NCI–H187, and Vero cells. Graphical abstract: Eight naturally undescribed compounds were isolated from the endophytic Streptomyces sp. TBRC7642 and biological activity of these compounds were reported. Image 1 Highlights: Eight naturally undescribed compounds were isolated from Streptomyces sp. TBRC7642. Chemical structures were determined by spectroscopic analysis. Absolute configurations were assigned by based on CD spectra and optical rotations. The isolated compounds were evaluated for biological activity and for cytotoxicity.